Electrical behavior and structure – property correlations in La1–xPrxMnO3 (0 ≤ x ≤ 1) ceramics. Issue 1 (January 2019) - Udeshi, Bhagyashree; Boricha, Hetal; Rajyaguru, Bhargav; Gadani, Keval; Rathod, K.N.; Dhruv, Davit; Kansara, S.B.; Trivedi, R.K.; Pandya, D.D.; Asokan, K.; Solanki, P.S.; Shah, N.A.
Abstract: In this communication, we report the results of the electrical studies on La1–x Prx MnO3 (LPMO; 0 ≤ x ≤ 1) single valent manganites synthesized by conventional solid state reaction route. Structural studies reveal a single phasic nature of all LPMO samples having orthorhombic unit cell structure without any detectable impurity or structural phase transformation. Dielectric constant and impedance are found to increase while ac conductivity gets suppressed effectively upon increase in Pr content (x). This has been discussed in detail on the basis of structural distortion and tolerance factor in LPMO manganites. Temperature dependent dielectric behavior indicates an anomaly near respective magnetic transition temperature. Obtained dielectric and ac conductivity results have been theoretically fitted using relaxation formula and power law, respectively. Obtained fitting parameters have been discussed in the context of various structural aspects of LPMO manganites.